Empathy, Film, and the Brain - Grodal, Torben; Kramer, Mette (Recherches sémiotiques / Semiotic Inquiry, 2010)
This article discusses the role of empathy based on evolutionary, human developmental, and neuropsychological theories in combination with film theory and analysis in order to explain the film viewer’s emotional reactions primarily to painful fictive scenarios.